Molecular Recognition of Spermine using Aggregation‐Induced Emission. Issue 8 (21st June 2018) - Hayduk, Matthias; Riebe, Steffen; Rudolph, Kevin; Schwarze, Sandrina; van der Vight, Felix; Daniliuc, Constantin G.; Jansen, Georg; Voskuhl, Jens
Abstract: In this communication we report the synthesis and characterisation of a novel dianionic compound with aggregation‐induced emission properties. This compound was able to recognize spermine via a multivalent electrostatic interaction leading to a restriction of intramolecular rotation enhancing the fluorescence emission. This recognition was investigated in detail using UV‐Vis and fluorescence spectroscopy. Furthermore the binding stoichiometry was determined via isothermal titration calorimetry. Besides that the structure of the compound was confirmed by X‐ray crystallography. To proof the bivalent binding a singly negatively charged control compound was synthesized showing no specific interaction with the amines screened. Theoretical calculations were performed to get a deeper insight in the molecular structure and the electronic transitions. Abstract :